Development of Heyzine Flipbook–Based Islamic Religious Education Learning Media to Improve Student Learning Outcomes at SMP IT Al-Mursi Tangerang (Jurnal Mu'allim, 2026)
This study was developed with the following objectives: (1) to determine how to create Islamic Religious Education (PAI) learning media using Heyzine Flipbook; (2) to determine the feasibility of Heyzine Flipbook–based PAI learning media; and (3) to determine how well the media benefits students at SMP IT Al-Mursi Tangerang. The researcher employed the 4D development model (Four-D Model), which consists of four stages: define, design, develop, and disseminate. This model is part of the Research and Development (R&D) research process. This study used validation questionnaires and test items to obtain data. The research instruments used in this study were expert validation sheets and pretest and posttest questions. This study applied qualitative descriptive analysis and quantitative n-gain analysis to draw conclusions from the obtained data. When the data from media experts, material experts, and Islamic Religious Education subject teachers were combined, the average scores obtained were 4.53 for media, 3.75 for material, and 4.58 for Islamic Religious Education as the content area. Based on the n-gain assessment criteria, the product testing results showed an average score of 0.43 on the pretest and posttest, which falls into the medium category. This indicates that students’ learning outcomes increased after using the PAI-based learning media called Heyzine Flipbooks.
Keywords: Learning Media, Heyzine Flipbooks, Learning Outcomes